Treatment Efficacy of Vernal Keratoconjunctivitis with 0.1 Percent Fluorometholone and 0.05 Percent Cyclosporine - Asna Tahir, Syed Shujaat Ali Shah, Muhammad Awais Ashraf, Muhammad Naeem, Lt Col Ayyaz Hussain Awan, Muhammad Zia Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to evaluate the efficacy of two common treatments for vernal keratoconjunctivitis: fluorometholone (0.1%) and cyclosporine (0.05%). Study Design: Comparative/prospective study Methods: Total 86 patients of vernal keratoconjunctivitis were included in this study. Two groups were equally created, group I received fluorometholone (0.1%) in 43 cases and group II received cyclosporine (0.05%)in 43 cases. To find the significant value, chi-square and unpaired t test procedures were employed. Results: There were 52 (60.5%) males and 34 (39.5%) females among all cases. There were 45 (52.3%) cases had age 5-10 years, 25 (29.1%) cases had age 11-15 years and 16 (18.6%) cases had age 16-20 years. Among all, itching and redness were the most common signs/symptoms. Frequency of efficacy in group I was 39 (90.7%) and in group II efficacy was found in 31 (72.1%) cases with p value <0.003. Frequency of systemic allergy was higher in group I as compared to group II <0.002. Conclusion: According to these findings, fluorometholone might be an improved option for treating severe vernal keratoconjunctivitis. It is important to take systemic allergy links into account when treating. Keywords: Cyclosporine, Fluorometholone, Vernal Keratoconjunctivitis